Analysis of Vibration Response of Rigid-flexible Coupled Subway Gear Transmission System - Qiu Xinghui; Yang Jianwei; Chen Zhongwei (Jixie chuandong)
The subway gearbox is a key vehicle transmission parts,its vibration condition affects the safety operation of the train. The dynamic response of the subway gearbox is studied,taking the physical model of the subway gearbox as the research object,the data conversion of the Cero and ADAMS data interface is carried out,and the gearbox is flexible by means of ANSYS. The rigid body is replaced by the flexible body,and make reasonable restraint to it. The model of gear contact is established,and the bearing pair is built by ADAMS built-in mechanical package module,and the rigid-flexible coupling dynamics model of subway gearbox is established. According to the simulation results of the gearbox dynamics analysis,the analysis of the box in the gear start and the acceleration phase there is a large vibration impact,and compare the stress and strain of the measured point of view,the upper box is significantly more than the box. The vibration response of the upper box and the upper part of the upper box are affected by the signal superposition and so on,the stress response can be considered. It is possible to consider the optimization of the box structure,consider adding the reinforcement and other measures to strengthen the dangerous node stability. It provides references for the design of subway gearbox.